Methods in ecological and agricultural entomology - Dent, David Ph. D.; Walton, M. P. (CAB International, 1997)
Aims to integrate new approaches and technologies with traditional and proven methods of ecological and agricultural entomology. This book provides an analysis and evaluation of the methods available, their application, and also the general principles involved.